An Analysis of the problems and cost efficiency of mergers between commercial banks and credit departments of farmers' associations in Taiwan - Lai, Wen-Quai (2010)
Even as Taiwan agriculture is in slump, Taiwan's Agricultural Society (the equivalent of Japan's agricultural cooperatives) still operate efficiently. The Agricultural Society's costs, particularly labor costs, are low compared with private entities' levels. Despite the operational efficiency of the Taiwan's Agricultural Society, its organizations' production is sluggish because of their weak infrastructure. In addition, the agricultural credit associations' problems on non-performing loans have become more serious. The study focuses on ways to analyze the problems and cost efficiency of emergers between commerical banks and the credit departments of farmers associations in Taiwan. Using business efficiency and analysis methods to analyze the management efficiency of the Agricultural Society, the study shows that operating expenses and personnel costs can still be decreased. To enhance operational efficiency, business scale expansion is needed through reforms to encourage healthy growth.
Keywords: Bank mergers